Are Patients With Autoimmune Cytopenias at Higher Risk of COVID-19 Pneumonia? The Experience of a Reference Center in Northern Italy and Review of the Literature - Barcellini, Wilma; Giannotta, Juri Alessandro; Fattizzo, Bruno (Frontiers in Immunology, 2021)
During COVID-19 pandemic the care of onco-hematologic and autoimmune patients has raised the question whether they are at higher risk of infection and/or worse outcome. Here we describe the clinical course of COVID-19 pneumonia in patients with autoimmune cytopenias (AIC) regularly followed at a reference center in Northern Italy. The study period started from COVID-19 outbreak (Februrary, 22 2020) until the time of writing. Moreover we provide a review of the literature, showing that most cases reported so far are AIC developed during or secondary to COVID-19 infection. At variance, data about AIC pre-existing to COVID infection are scanty. The 4 patients here described (2 autoimmune hemolytic anemias, AIHA, 1 Evans syndrome, and 1 immune thrombocytopenia) with COVID-19 pneumonia belong to a large cohort of 500 AIC patients, making this study nearly population-based. The observed frequency (4/501; 0.7%) is only slightly superior to that of the general population admitted to hospital/intensive care unit (0.28/0.03%, respectively) in Lombardy in the same period of observation. All cases occurred between March, 21 and 25, whilst no more AIC were recorded later on. Although different in intensity of care needed, all patients recovered from COVID-19 pneumonia, with apparently no detrimental effect of previous/current immunomodulatory treatments. AIHA relapse occurred in two patients, but promptly responded to therapy. With limitations due to sample size, these results suggest a favorable outcome and a lower-than expected incidence of COVID-19 pneumonia in patients with previously diagnosed AIC, and allow to speculate that immunomodulatory drugs used for AIC may play a beneficial rather than a harmful effect on COVID-19 infection.